Preventing Local Government Fraud Through Supervision of Local Development Planning (Case Study on Supervision by X Province to Y Regency) - Jiwa Muhamad Satria Nusantara; Irfan Ridwan Maksum (Asia Pacific Fraud Journal, 2021)
Supervision from the Governor as the representative of the central government to the Regencies/cities below, becomes one of the factors in the consistency of development planning and budgeting, Sugiarto (2015). As a Regency with the highest growth rate in X Province, X Provinceshould pay attention to supervise local development planningin Y Regency to prevent Fraud. In fact, the role of the governor to supervise Y Regency still meet some obstacles. The analysis in this research is using the policy implementation model of Meter and Horn (1975), the supervision process by Griffin (2004) and the factors that influence the supervision of Tugiman (1996). Through a descriptive qualitative research approach, research analyses the implementation and the influencing factors of the implementation of the local development planning supervision policy of Y Regency by X Province. The results of the research show that policy implementation is not optimal and can be the starting point of fraud and corruption in local government. Some of the conditions that are not yet optimal in supervision include, dilemma in policy implementation, inaccurate determination of supervisory indicators, limitations in organizational structure, inappropriate monitoring budgeting mechanisms, and political bias between levels of government.Recommendations from this study include, government should to revise several regulations related to the role of the governor as the representative of the central government, revise indicators that related to local development planning supervision, work patterns that are not tied to organizational structures, preparation of SOPs and information systems that are used as tools for implementing supervision.